Analisis Keberlanjutan Objek Wisata Air Bojongsari di Kabupaten Purbalingga, Indonesia - Panggalih, Chandra Arif; zumaeroh, Zumaeroh; Jati, Damar; Purnomo, Sodik Dwi (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
Bojongsari Water Tourism Object (Owabong) is one of the tourist attractions that shows water tourism. Owabong in the period of 8 years from 2016-2023 experienced fluctuations, in 2019 the number of visitors to Owabong decreased slightly by 5.78%, this was because the beginning of the Covid-19 pandemic greatly affected tourism in Owabong. So that in 2020 the number of visitors dropped drastically by 57.44% and was followed by 31.91% in 2022. so that policies are needed that support creating sustainable Owabong. This study aims to determine the sustainability of the Bojongsari water tourism object (Owabong) in Purbalingga Regency. The analysis method used in this study is Multidimensional Scaling (MDS) for sustainability analysis consisting of 5 dimensions, namely Ecological, Economic, Socio-Cultural, Legal and Institutional dimensions, and Technological Infrastructure. The results of the sustainability of each dimension can be stated that the Ecology dimension is 53.22, Economy 59.37, Socio-Cultural 57.37 Law and Institutions 74.79 and Technological Infrastructure 56.83 which all fall into the fairly sustainable status, the sustainability index value is 60.31 which is classified as fairly sustainable. The implications of this study are 1) By conducting continuous education; 2) Cooperating with travel agents; 3) Providing disability-friendly facilities; 4) Accountability and transparency and; 5) Improving the quality of service.